Flamecaster : A Shattered Realms Novel - Chima, Cinda Williams (New York Happer Teen, 2016)
Thrown together by chance and united by their hatred of the king, Ash, a gifted healer, and Jenna, a girl abandoned at birth, find themselves on the run from the King's Guard.
Keywords: Revenge -- Magic -- Healers -- Fantasy